TRENDS IN MODERN EXTREMISM: CHALLENGES AND LESSONS - Djoric, Marija (Political Review, 2023)
Extremism as a social phenomenon is extremely dynamic – it is conditioned not only by time and space, but also by a constellation of different socio-political relationships. The paper deals with the analysis of the most important trends in contemporary forms of extremism, with a special focus on existing security challenges. The author first elaborated all the controversies that are related to the problem of defining extremism and familiar phenomena, in order to continue the work to point out the following trends that affect the change in the perception of modern forms of extremism, such as: the influence of modern technique and technology, the “individualization” of extremism, ideological controversies and the gender approach to the study of this phenomenon. The emergence of artificial intelligence (AI), 3D printed weapons, hybrid ideologies, the multiplication of communication in the online space and the change of methods and means of action are just some of the contemporary challenges that benefit extremists, while at the same time making it difficult for theorists and practitioners in this field. We should not forget the intensification of the gender issue (and gender approach) in the context of extremism, because there are more and more misogynistic extremist organizations, while the role of women in the context of extremism is still contradictory. The research methods are based on document content analysis, case studies and comparative analyses. The conclusion is that modern violent extremism is a dynamic phenomenon, which must be constantly monitored, if we want to identify its changes, and therefore draw certain lessons, which would enable successful prevention (PVE).